2014
DOI: 10.1371/journal.pntd.0003210
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leishmaniasis and Sand Fly Fluctuations Are Associated with El Niño in Panamá

Abstract: BackgroundCutaneous Leishmaniasis (CL) is a neglected tropical vector-borne disease. Sand fly vectors (SF) and Leishmania spp parasites are sensitive to changes in weather conditions, rendering disease transmission susceptible to changes in local and global scale climatic patterns. Nevertheless, it is unclear how SF abundance is impacted by El Niño Southern Oscillation (ENSO) and how these changes might relate to changes in CL transmission.Methodology and FindingsWe studied association patterns between monthly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 79 publications
(107 reference statements)
1
45
0
6
Order By: Relevance
“…A study conducted in Panama indicated an increase in the occurrence of cutaneous leishmaniasis (CL) during the ENSO cold phase (La Niña). (16) In Ven- ezuela, between 1994 and 2003, a significant negative association between CL cases and ENSO was also observed. A significant number of CL cases were reported during the cold phase/La Niña; moreover, in that study, the authors observed that during the years where higher ENSO variation was observed, the incidence of CL was lower.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A study conducted in Panama indicated an increase in the occurrence of cutaneous leishmaniasis (CL) during the ENSO cold phase (La Niña). (16) In Ven- ezuela, between 1994 and 2003, a significant negative association between CL cases and ENSO was also observed. A significant number of CL cases were reported during the cold phase/La Niña; moreover, in that study, the authors observed that during the years where higher ENSO variation was observed, the incidence of CL was lower.…”
Section: Discussionmentioning
confidence: 86%
“…A similar pattern seems to influence sandflies as there is a decrease in the abundance of the species due to an increase in temperature. (16) Moreover, digestion, metabolic processes, and the development of different species of sandflies are significantly affected by ambient temperature. (25) Moreover, the development of a parasite in a vector is also influenced by environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This sensitivity arises because the climate directly affects the abundance of sand‐flies and how quickly the parasites replicate . Association patterns of CL and sand fly abundance with climate change events like ENSO have been shown in many parts of the world . In addition, temperature is an important factor in regulating the morphogenesis and growth of disease parasite .…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, se encontró que el patrón definido de LC se debe principalmente a la estacionalidad. Estos resultados son similares a los presentados por varios autores, que analizan el impacto de la variabilidad climática (El Niño y la Niña) en un corto periodo de tiempo para la leishmaniasis cutánea en Venezuela (Cabaniel et al, 2005), Colombia (Cárdenas et al, 2006), Costa Rica (Chaves & Pascual, 2007) y Panamá (Chaves et al, 2014).…”
Section: Discussionunclassified
“…Sin embargo, son escasos los artículos enfocados en el nicho ecológico de Leishmania spp. (King, Campbell-Lendrum, & Davies, 2004;Nieto, Malone, & Bavia, 2006;Moo-Llanes et al, 2013;Samy, Campbell, & Peterson, 2014;Piggot et al, 2014a;Rajabi, Mansourina, Pilesjo, & Bazmani, 2014); en contraste, con los principales temas que son la distribución espacio-temporal (Feijó et al, 2012;Mollalo, Alimohammandi, Shirzadi, & Malek, 2015), identificación de áreas de riesgo (Carneiro et al, 2007;Salahi-Moghaddam, Mohebali, Moshfae, Habibi, & Zarei, 2010;Almeida, de Andrade, & Werneck, 2011;Seid et al, 2014), determinar la asociación de El Niño con casos de LC y flebotomineos (Cabaniel, Rada, Blanco, Rodríguez-Morales, & Escalera, 2005;Chaves & Pascual, 2007;Chaves, Calzada, Valderrama, & Saldaña, 2014), variabilidad climática de los casos de leishmaniasis (Cárdenas, Sandoval, Rodríguez-Morales, & Franco-Paredes, 2006) y correlación espacial entre Leishmania spp. y flebotomineos (Chelbi, Kaabi, Bejaoui, Derbali, & Zhioua, 2009).…”
unclassified